Monitoring of Immovable Cultural Heritage Implementing 3D and Artificial Intelligence Technologies - Laužikas, Rimvydas; Kuncevičius, Albinas; Amilevičius, Darius; Žižiūnas, Tadas; Šmigelskas, Ramūnas (Archaeologia Lituana, 2019)
Preservation of immovable cultural heritage is one of the main challenges for contemporary society. Nowadays very often organizations responsible for heritage management constantly have to deal with lack of resources, which are crucial for proper heritage preservation, maintaining and protection. The possible solution of these problems could be automated heritage monitoring, based on the 3D and AI technologies. 3D scanning technology is the most accurate method to capture the situation of an evolving cultural heritage object or complex at a given time. As a cultural heritage object or complex is evolving continuously, AI based comparison of two 3D point clouds created at different time allow to reliably trace potential changes. Proposed solution is realized by project financed by Research Council of Lithuania „Automated monitoring of urban heritage implementing 3D technologies”. The first results of the project are presented at this article.